(untitled) (International journal of artificial intelligence, 2026)
The article examines the trends, challenges, and prospective directions of innovative modernization of the banking sector of the Khorezm region based on digital technologies and remote banking services. Digitalization is considered a key driver of the transformation of the global financial system and contributes to increasing the efficiency of banking operations, expanding access to financial services, and enhancing financial inclusion of the population. Using statistical data from the Central Bank of the Republic of Uzbekistan and government agencies, the dynamics of non-cash payments, the development of mobile banking, and the expansion of the acquiring infrastructure in the region are analyzed. The main barriers to digitalization are identified, including digital inequality between urban and rural areas, insufficient digital literacy of the older population, low confidence in online transactions, and infrastructural limitations. The article proposes directions for the modernization of the regional banking sector, such as the development of digital infrastructure, improvement of financial literacy, standardization of mobile banking applications, and implementation of the “Digital Bank 2.0” model. Implementation of the proposed measures will increase the share of online services, reduce operating costs of banks, and strengthen the role of digital services in the socio-economic development of the Khorezm region.